2018
DOI: 10.1016/j.jaim.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Selective Estrogen Receptor Modulator and prostimulatory effects of phytoestrogen β-ecdysone in Tinospora cordifolia on osteoblast cells

Abstract: BackgroundIndian ethnomedicine acclaims Tinosporacordifolia as a bone strengthening agent and prescribes it for the treatment of bone fractures, gout and other inflammatory diseases of the bone.Objective(a) To understand the potential of T. cordifolia to act as a Selective Estrogen Receptor Modulator (SERM) on in vitro models. (b) To understand the toxic effects (if any) of T. cordifolia in vivo. (c) To understand the effects of β-ecdysone (proposed osteoprotective principle of T. cordifolia) on the growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Magnoflorine, besides being one of the marker phytocompounds of T. cordifolia , is associated with anti-nephro ( Gupta and Sharma, 2011 ) and anti-hepatotoxic ( Sharma and Dabur, 2015 ) effects. Likewise, β-ecdysone, along with remarkable anti-osteoporotic and bone-protective properties, is reported to be cytologically safe ( Abiramasundari et al, 2018 ). Therefore, the phytoconstitutional integrity and traceability of TCWE safety was established through UHPLC with the marker compounds, magnoflorine and β-ecdysone.…”
Section: Resultsmentioning
confidence: 99%
“…Magnoflorine, besides being one of the marker phytocompounds of T. cordifolia , is associated with anti-nephro ( Gupta and Sharma, 2011 ) and anti-hepatotoxic ( Sharma and Dabur, 2015 ) effects. Likewise, β-ecdysone, along with remarkable anti-osteoporotic and bone-protective properties, is reported to be cytologically safe ( Abiramasundari et al, 2018 ). Therefore, the phytoconstitutional integrity and traceability of TCWE safety was established through UHPLC with the marker compounds, magnoflorine and β-ecdysone.…”
Section: Resultsmentioning
confidence: 99%
“…The wide-spectrum therapeutic activities of T. cordiofolia are due to the presence of numerous key bioactive compounds. T. cordiofolia was shown to be responsible for five phyto-constituents out of ten in the current investigation, these are gallic acid, magnoflorine, rutin, β-ecdysone and rosmarinic acid [ 22 24 ]. Aloe barbadensis or Aloe vera, has been classically used for skin disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoecdysteoids have been identified in more than 100 plant families and plants are capable of biosynthesis of these from mevalonic acid, unlike insects ( Adler and Grebenok, 1995 ). The most commonly found phytoecdysteroid is 20-hydroxyecdysone (beta-ecdysone) and has also been identified in T. cordifolia ( Abiramasundari et al, 2018 ) and has been demonstrated to induce osteogenic transformation. They have been shown to have immunomodulatory activity wherein the concentration of antibody forming B cells in the spleen of mice immunized with sheep RBC was higher (Sakhibov et al, 1989).…”
Section: Discussionmentioning
confidence: 99%